Cutoff Values of Hemodynamic Parameters in Pediatric Refractory Septic Shock - En-Pei Lee; Jainn-Jim Lin; Shao-Hsuan Hsia; Oi-Wa Chan; Sheng-Ling Jan; Han-Ping Wu (MDPI AG, 2022)
Background: Refractory septic shock can cause severe morbidities and mortalities in children. Resuscitation based on hemodynamics is important in children with critical illness. Thus, this study aimed to identify the hemodynamics of refractory septic shock associated with poor prognosis at an early stage to allow for timely interventions. Methods: We evaluated children with refractory septic shock admitted to a pediatric intensive care unit (PICU) and monitored their hemodynamics using a pulse index continuous cardiac output (PiCCO) system. The serial cardiac index (CI), systemic vascular resistance index (SVRI), and vasoactive-inotropic score (VIS) were recorded during the first 72 h after PICU admission. Results: Thirty-three children with refractory septic shock were enrolled. The SVRI and VIS were both associated with fatality from septic shock. The non-survivors had lower serial SVRI and higher VIS (both p < 0.05). Based on the area under the ROC curve, the SVRI was the predictor during the early resuscitative stage (first 36 h) in pediatric refractory septic shock. Conclusions: Both SVRI and VIS are predictors of mortality in children with refractory septic shock, and the SVRI is the powerful predictor of mortality in the early resuscitative stage. A low serial SVRI may allow for the early awareness of disease severity and strategies for adjusting vasoactive-inotropic agents to increase the SVRI.